Nobody tought us that way but.. water and oil do form homogeneous mixtures - D'Acunha Sandoval, Brenda (2010)
The Ig Nobel is a prize awarded since 1991 by the journal “Annals of Improbable Research” along with Harvard University. The prizes are intended to “celebrate de unusual,honor the imaginative and spur people’s interest in science, medicine, technology and other areas” according to their creators (http://improbable.com/ig). By rewarding different investigations that look funny to the common people, the Ig Nobel seeks to make people laugh and then think.